Perbedaan Infeksi Malaria di Daerah Dataran Tinggi dan Dataran Rendah di Jayapura - Reni Marlina Titihalawa (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Malaria remains a global health problem of ongoing international concern. This study aimed to determine whether there is a significant difference in malaria infection cases between highland and lowland areas in Jayapura City. The study employed an exploratory research design with a cross-sectional approach. The data used were secondary data of malaria-positive patients diagnosed at six public health centers (Puskesmas) in Jayapura. Three Puskesmas represented lowland areas (Hamadi, Abe Pantai, and North Jayapura), while three represented highland areas (Harapan, Sentani, and Nimbokrang). The case data were statistically analyzed using a Paired Sample T-Test. The results showed that the total number of positive malaria cases recorded in the three lowland Puskesmas was 1,608 cases, whereas the three highland Puskesmas recorded a total of 8,056 positive malaria cases. The Paired Sample T-Test yielded a significance value of 0.003 (p < 0.005). In conclusion, there is a significant difference in malaria infection between highland and lowland areas in Jayapura City. Malaria infection cases are substantially higher in highland areas compared to lowland areas